Composição florística do Museu de História Natural e Jardim Botânico da Universidade Federal de Minas Gerais, Belo Horizonte, Minas Gerais - Demian Ferreira Felix (2009)
Floristic composition of the Natural History Museum and Botanic Garden of Universidade Federal de Minas Gerais, Belo Horizonte, Minas Gerais. The conservation and study of urban remnants are today neglected regarding the national parks and large biological reserves. Consequently, the flora and ecology of these environments are little known. The goal of this work was to analyze the floristic composition of the native remnants of the Natural History Museum and Botanical Garden of Universidade Federal de Minas Gerais (MHNJB) and compare the data with other studies in urban fragments of the southeastern Brazil. The study area has been known as Horto florestal, Experimental Station, Agronomic Institute, Natural History Museum, and currently, MHNJB. Has about 60 ha, headquarters located at 19°53,496`S and 43°54,959`W, at 830m of altitude in average, belonging to the Arrudas stream basin. For the floristic inventory, monthly collections were made in seven different areas, during a year. The phytophysiognomies descriptions were made using diagram profiles and ecological observations like sucessional stage and general state of conservation of the forests fragments. In the vascular plant inventory, 399 species were sampled, belonging to 285 genera and 88 families. The MHNJB flora consists of 43% of autochthonous, 40% of allochthonous species and 17% of unspecified locality. Counting the total number of studied species, the most representative families in species richness were Fabaceae (49), Rubiaceae (27), Myrtaceae (17), Malvaceae (16), Asteraceae (15), Bignoniaceae (15), Solanaceae (15), Poaceae (14), Acanthaceae (13) e Melastomataceae (11), what represents almost half of the species listed. The richest genera were Psychotria (11), Nectandra (4), Miconia (3), Ocotea (3), Senna (3) e Solanum (3). The predominant habit was tree, with 60% of the species, followed by bushes (18%), herbaceous (15%), and vines (5%), the epiphytic flora is poor represented, with less than 3% of the total. Two autochthonous and threatened species, Dalbergia nigra e Melanoxylon brauna (Fabaceae), are found in the area. A comparison between the sampled areas showed that the MHNJB consists in a mosaic of fragments in distinct successional stages. The MHNJB beyond of being an important area of leisure to the population, composes an important remnant of the original semidecidous forest of the Velhas river basin, nowadays almost destroyed by the human occupation.